Uso de pesticidas en hortalizas y su percepción sobre la salud en agricultores de la carretera Santa Clara, Loreto, 2023 - Aspajo Soria, Fernando (2025)
Intensive and improper use of pesticides in agriculture poses significant risks to farmers’ health and the environment. This research aimed to analyze pesticide use and perceptions of their health and environmental impacts among farmers on the Santa Clara road, Loreto, in 2023. Based on theories of pesticide toxicity, safe agricultural practices, and risk perception, a descriptive study was conducted using structured surveys with local horticulturists. Results indicated that most farmers apply pesticides monthly or occasionally, with chemical pesticides predominating over organic ones. Low use of personal protective equipment and reliance on informal recommendations for pesticide selection were identified. Additionally, a significant percentage of farmers reported respiratory problems, skin irritation, and dizziness, symptoms associated with duration and frequency of exposure. Environmental perception was moderate and varied according to educational level. It is concluded that there is an urgent need to strengthen education, promote safe practices, and enforce adequate regulations to minimize adverse effects and foster agricultural sustainability in the region.